Giovanni di Paolo the onset of an artistic extravaganza : apprenticeship and early career (1410-1426) - Freuler, Gaudenz 1949- (Darte, 2024)
The present study focuses on his apprenticeship (c.1410-1417) and - in light of a newly rediscovered early Virgin of Humility - his subsequent development as he broke away from his first teachers (1417-1426). The second part of the volume offers a survey of Giovanni di Paolo’s biography and career, with a discussion of some of his dated works
Enthält 166 Illustrationen
Keywords: Giovanni -- di Paolo -- 1398-1482